2014
DOI: 10.1007/s10295-014-1527-z
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of specific proton motive force-dependent transporters facilitate the export of surfactin in Bacillus subtilis

Abstract: A novel surfactin producer, Bacillus subtilis THY-7, was isolated from soil. Using liposomes and transmembrane transport inhibitors, the surfactin efflux in THY-7 was determined to be mainly dependent on proton motive force (PMF), not ATP hydrolysis. YcxA, KrsE and YerP, three putative lipopeptide transporters with PMF as energy source, were then highlighted in this work. A mutant YcxA named as YcxAmt, with 2 transmembrane helices deletion due to a code-shift mutation of the encoding gene, was identified in TH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 48 publications
0
44
0
2
Order By: Relevance
“…The wild surfactin producer, B. subtilis THY‐7, was isolated from a soil sample and deposited at the China General Microbiological Culture Collection Center (CGMCC No. 8906) (Li et al, ). E. coli TOP10 were used for gene cloning and plasmid construction, and E. coli BL21 were used for lacZ reporter gene cloning.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The wild surfactin producer, B. subtilis THY‐7, was isolated from a soil sample and deposited at the China General Microbiological Culture Collection Center (CGMCC No. 8906) (Li et al, ). E. coli TOP10 were used for gene cloning and plasmid construction, and E. coli BL21 were used for lacZ reporter gene cloning.…”
Section: Methodsmentioning
confidence: 99%
“…Surfactin concentrations were determined by high performance liquid chromatography (HPLC) using an LC‐20A HPLC system (Shimadzu, Kyoto, Japan) equipped with an ODS‐SP column (250 × 4.6 mm, 5 μm; GL Sciences, Kyoto, Japan) and a DA detector (Shimadzu) as previously described by Li et al (). Surfactin standards were purchased from Sigma (Shanghai, China), and experiments were performed in triplicate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…cereus group strains, but a recent study demonstrated that an orthologous pump is involved in the efflux of a surfactin in B . subtilis [37]. Surfactin has been shown by a number of studies to be essential for formation of mature biofilms by B .…”
Section: Resultsmentioning
confidence: 99%
“…subtilis (Table 4). Functional analyses of YerP recently demonstrated that overexpression of this pump in its native host resulted in increased secretion of endogenously produced surfactin into the supernatant [37]. YerP is also known to be involved in surfactin resistance in strains that do not produce an endogenous surfactin and can mediate resistance to acriflavine and ethidium [50].…”
Section: Resultsmentioning
confidence: 99%